PENDAMPINGAN PARENTING DALAM MEMBANGUN KESADARAN DAN KEDISIPLINAN ANAK USIA DINI - Zuhriyah, Nunik; Firdaus, Zakaria; Muhaimin, M Zunaidul (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
Strengthening the role of parents in educating children from an early age is the main key in shaping disciplined and responsible characters. This community service program aims to provide parenting assistance to parents in building awareness and discipline of early childhood through effective parenting. This activity is carried out through socialization, training, and direct assistance to parents in the school environment. The results of this program show that parenting assistance that involves effective communication, positive role modeling, and consistent application of rules has a significant impact in increasing children's awareness of responsibility and self-discipline. In addition, active participation of parents in accompanying children's development also contributes to the formation of better character. With this activity, it is hoped that parents can better understand the importance of their role in shaping children's behavior patterns and be able to apply appropriate parenting strategies to support optimal child development